2007
DOI: 10.1007/s11214-007-9173-7
|View full text |Cite
|
Sign up to set email alerts
|

The Solar Chemical Composition

Abstract: We present our current knowledge of the solar chemical composition based on the recent significant downward revision of the solar photospheric abundances of the most abundant metals. These new solar abundances result from the use of a 3D hydrodynamic model of the solar atmosphere instead of the classical 1D hydrostatic models, accounting for departures from LTE, and improved atomic and molecular data. With these abundances, the new solar metallicity, Z, decreases to Z = 0.012, almost a factor of two lower than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

52
809
5
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 731 publications
(881 citation statements)
references
References 31 publications
52
809
5
1
Order By: Relevance
“…Keeping the values of log g that we determined in the first stage of the phoebe analysis, rotational velocities calculated under the assumption of tidal locking (which were consistent with preliminar spectral analysis results), and solar abundances pattern fixed (Grevesse et al 2007), we fitted for T eff and [M/H]. As starting values, we used the temperatures we adopted from phoebe analysis (brighter component effective temperature based on the colour-temperature calibration from Worthey & Lee 2011) and solar metallicity.…”
Section: Spectral Analysissupporting
confidence: 62%
“…Keeping the values of log g that we determined in the first stage of the phoebe analysis, rotational velocities calculated under the assumption of tidal locking (which were consistent with preliminar spectral analysis results), and solar abundances pattern fixed (Grevesse et al 2007), we fitted for T eff and [M/H]. As starting values, we used the temperatures we adopted from phoebe analysis (brighter component effective temperature based on the colour-temperature calibration from Worthey & Lee 2011) and solar metallicity.…”
Section: Spectral Analysissupporting
confidence: 62%
“…There is one free parameter (α), so for the abundance to be 264 significant at the 3-σ level ∆χ 2 = χ 2 (α opt ) − χ 2 (0) must be less than -9 265 (Press et al, 1992). In the case of no significant minimum, the 3-σ upper (2002) and Lellouch et al (2002) • If the chlorine source is from comets, a solar Cl/O ratio of 6.9 × 10 −4 299 is reasonable (Grevesse et al, 2007), implying a chlorine flux of 2.8 × 300 10 3 molecules/cm 2 /s. IDPs and micrometeorites can be discounted 301 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 as they would not result in sufficient CO production, but would also 302 provide a similar chlorine flux.…”
Section: Hcl Upper Limits 254mentioning
confidence: 96%
“…HCl 3 abundance is expected to be extremely variable throughout the atmospheric 4 column and will depend strongly on local atmospheric conditions and the 5 nature of the source reservoir. At the most basic level, Jupiter's bulk chlo-6 rine abundance can be estimated from the solar chlorine to hydrogen ratio of 7 3.2×10 −6 (Grevesse et al, 2007) combined with the observation that Jupiter 8 is enriched in heavy elements, such as carbon, relative to the solar compo-9 sition by a factor of about four (Niemann et al, 1998;Wong et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…They found oxygen and nitrogen gradients essentially flat, and in good agreement with our results (see Table5 The comparison between the H ii region and blue supergiant populations is extremely interesting because they both are young populations and should trace the same epoch in the galaxy lifetime. In the upper panel of Figure 4 we plotted the metallicity of the supergiants of Kudritzki et al (2016) and of our H ii regions -reported on the Solar scale (12+log(O/H)=8.66; Grevesse et al 2007)-versus the galactocentric distance. We have plotted the whole sample of Kudritzki et al (2016) without removing the possible outliers.…”
Section: Radial Abundance Gradients In Ngc 55mentioning
confidence: 99%